Outcome of bipolar transurethral resection in benign enlargement of prostate - Shrestha, Samir; Maskey, Pukar; Shah, Jay N (Journal of General Practice and Emergency Medicine of Nepal, 2021)
Introduction: Lower urinary tract symptoms (LUTS) secondary to benign enlargement of prostate (BEP) is one of the common urological problem in men. Bipolar transurethral resection of prostate (B-TURP) is a standard surgical intervention for BEP. In this study we aim to analyze the perioperative outcome and complications of B-TURP for BEP. Method: This retrospective study analyzed the perioperative outcome & complications of B-TURP in patients with BEP from August 2017 to July 2020at Patan Hospital, Patan Academy of Health Sciences, Lalitpur, Nepal. Data was collected from the operating room register and from inpatients files from the record section. SPSS version 16 was used to analyze the data. Study variables included age, ASA grade with known concomitant comorbidities, prostate volume, total prostate specific antigen (TPSA), operative time, decreased hemoglobin level, postoperative bladder irrigation duration, hospital stay, transurethral resection syndrome (TURS), hyponatremia, blood transfusion, postoperative hematuria requiring intervention, postoperative acute urinary retention, urinary tract infection (UTI) and urine incontinence. Result: A total of 72 patients underwent B-TURP. Data was analyzed on 46 patients. Those with incomplete data and those files which were unable to retrieve were not analyzed. Perioperative outcomes were: median operative time was 81.73 minutes, median hospital stay was 3.4 days, median decreased hemoglobin was 3.0 g/dl and median postoperative bladder irrigation duration was 22.50 hours. Perioperative complications were: hyponatremia in 1 (2.1%), postoperative urinary retention in 2 (4.3%), blood transfusion in 4 (8.6%), postoperative hematuria requiring intervention in 3(6.5%), urinary incontinence in 8(17.3%) & urethral stricture in 6 (13.0%). There were no TURS & mortalities. Conclusion: Our study shows B-TURP is safe procedure with minimal morbidity for the treatment of benign enlargement of prostate.